(untitled) - L Florentinl (Rome, 1997)
This study makes use of the recently published ( FAO 1995 ) 45 year time series ( 1950 - 1994 ) of landings now available from FAO through the program FISHTAT-PC ( Version 5094/96 of March 1996 ) to analyse long-term trends and separate them automatically in a number of categories using an expert system for data analysis. Landing time series of the most important commercial speciesand group of species of both West ( 148 species ) and East ( 137 species ) Mediterranean have been processed with this program written in Pascal, in order to analyse and cotegorize long and short-term trends in these fisheries. Species trends have been caregorized following a discription of the differen stages a fishery could pass through in time ( new, rising, stable, declining, recovering and collapsed fisheries ). Species have been also arranged into ecological or biological categories ( estuarine, benthic and coastal, pelagic, large pelagic, demersal and slope resources ), and differences between West and East Mediterranean trends were sough for the same and different species. A ranking of the most important commercial species using 1992 catches, as well as by 1992 total value of landings, have been carried out, and a comparison between West and East Mediterranean fisheries has been provided.
Keywords: fisheries